Analysis Employment Changes in Tourism Sector and It’s Impact on Balanced Regional Development (Case Study: Gilan Province) - Mohammad Eskandari Noudeh; Ahmad Pourahmad; Mghgan Khoshdelan (جغرافیا و پایداری محیط)
Tourism regional planning to prevent unbalanced development of tourism destinations is one of the important issues in development tourism industry in developing countries. For tourism regional planning, identification regions position relative to each other is necessary. The concept of development included balanced distribution in addition to growth in all directions. Employment that is the most important economic indicators for evaluating the balanced development in national and regional levels is the main economic benefits of tourism. This study has investigated employment changes in tourism sector and it’s impact on balanced regional development in Gilan province during two time periods 1996-2006 and 2006-2011. The research method is descriptive–analytical. Information needed has collected relying on documentary research. For analyze employment changes in tourism sector has used number of employees "activities related to provide accommodation and food" as an alternative in this field. Our findings by using shift-share analysis, LQ and entropy models indicates that during in this tow period employment in tourism sector has been positive growth in province. While it’s distribution in county province has been along balanced regional development on period 1996-2006 and hasn't been in this regard on period 2006-2011. In the first period, except the county of Astara, Rasht, Shaft and Sowmee- Sara and Fooman, other counties has been more growing than province in this part of the province's economy and on period 2006-2011, except the county of Rasht, Roudsar, Lahijan and Masal that has been more growing than province, 12 other county has been negative growth in this regard. Additionally, during the first period Fouman, Astaneye-Ashrafieh and Langeroud counties and during the second period Rasht, Amlash and Lahijan counties have been the most successful operation in the field of increasing the share of employment in tourism sector.